Brazilian Consensus on the management of inflammatory bowel diseases in pediatric patients: a Consensus of the Brazilian Organization for Crohn’s disease and colitis (GEDIIB) - Lomazi, Elizete Aparecida; Oba, Jane; Rodrigues, Maraci; Marmo, Michela Cynthia da Rocha; Sandy, Natascha Silva; Sdepanian, Vera Lucia; Imbrizi, Marcello; Baima, Júlio Pinheiro [UNESP]; Magro, Daniéla Oliveira; de ALBUQUERQUE, Idblan Carvalho; Zabot, Gilmara Pandolfo; Cassol, Ornella Sari; et al. (FapUNIFESP (SciELO), 2022)
Background – Approximately 25% of patients with inflammatory bowel disease (IBD) develop the disease during childhood or adolescence and treatment aims to control active symptoms and prevent long-term complications. The management of Crohn’s disease (CD) and ulcerative colitis (UC) can be especially challenging in children and adolescents, related to particularities that may affect growth, development, and puberty. Objective – This consensus aims to provide guidance on the most effective medical and surgical management of pediatric patients with CD or UC. Methods – Experts in Pediatric IBD representing Brazilian gastroenterologists (Brazilian Organization for Crohn’s Disease and Colitis [GEDIIB]) developed this consensus. A rapid review was performed to support the recommendations/statements. Medical and surgical recommendations were structured and mapped according to the disease type, disease activity, and indications and contraindications for medical and surgical treatment. After structuring the statements, the modified Delphi Panel methodology was used to conduct the voting. The process took place in three rounds: two using a personalized and anonymous online voting platform and one face-to-face. Whenever participants did not agree with a specific recommendation, an option to explain why was offered to enable free-text responses and provide the opportunity for the experts to elaborate or explain disagreement. The consensus of recommendations in each round was accepted when reached ≥80% agreement. Results and conclusion – The recommendations are presented according to the stage of treatment and severity of the disease in three domains: management and treatment (drug and surgical interventions), criteria for evaluating the effectiveness of medical treatment, and follow-up/ patient monitoring after initial treatment, follow-up/ patient monitoring after initial treatment. Surgical recommendations were grouped according to disease type and recommended surgery. The target audience for this consensus was general practitioners, gastroenterologists, and surgeons interested in the treatment and management of pediatric CD and UC. Additionally, the consensus aimed to support the decision-making of health insurance companies, regulatory agencies, and health institutional leaders and/or administrators.
Consenso brasileiro de manejo das doenças inflamatórias intestinais em pacientes pediátricos: Consenso da Organização Brasileira para doença de Crohn e colite (GEDIIB)
Keywords: adolescents, inflammatory bowel diseases; children; colitis ulcerative; Crohn disease; disease management; surgery